Power (Re)distribution: How Dominant Capital Regained Control of the Energiewende - Tia Levi; Emil Israel; Max Grubman (Zeitschrift für Politikwissenschaft, 2024)
The Energiewende (energy transition) is the dynamic and contested project of energy transition in Germany. It encompasses both the sociotechnical transformation of the German electricity system and the reorganization of the sector's ownership structure. In this paper, we present a Capital-as-Power (CasP) based analysis, investigating industrial path-dependency and innovation as part of the dialectics of power and sociotechnical change in capitalism. According to CasP, dominant capital seeks to increase its differential accumulation, i.e., accumulation relative to a benchmark. Energiewende policies initially decreased the differential accumulation of dominant electricity firms in Germany. However, we find that by concentrating their control over the shrinking conventional generation capacity, while variable generation expanded, dominant firms gained the leverage needed to increase differential prices and profits, thus managing to regain sectoral control by increasing their threat to reliable power supply. We find that these processes coincide with spatial centralization, ownership concentration, and decreasing penetration rates of renewable energy resources in Germany. By presenting new conceptual tools and empirical findings, we trace the ways in which the recovery of dominant capital in the German electricity sector shapes and restricts energy transition processes.
Keywords: P1; P18; P11; P12; Q4; Q42; 330; energy transition; power; capitalism; political economy; electricity